Making ministry work a guide to serving together - Collins, Alan Walker, 1930-; Joint Board of Christian Education (Melbourne, VIC JBCE, 1996)
Includes bibliographical references.
Keywords: Church work -- Uniting Church in Australia; Clergy -- office -- Australia; Church management -- Australia